2013
DOI: 10.1593/tlo.13136
|View full text |Cite
|
Sign up to set email alerts
|

Anti-VEGFA Therapy Reduces Tumor Growth and Extends Survival in a Murine Model of Ovarian Granulosa Cell Tumor

Abstract: Although angiogenesis has been proposed as a therapeutic target for the treatment of ovarian granulosa cell tumor (GCT), its potential has not been evaluated in controlled studies. To do so, we used the Pten (tm1Hwu/tm1Hwu); Ctnnb1 (tm1Mmt/+);Amhr2 (tm3(cre)Bhr/+) (PCA) mouse model, which develops GCTs that mimic the advanced disease in women. A monoclonal anti-vascular endothelial growth factor A (VEGFA) antibody was administered weekly to PCA mice beginning at 3 weeks of age. By 6 weeks of age, anti-VEGFA th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…New treatment strategies need to be explored. The employment of anti-VEGFA antibody in mouse model successfully slowed the tumor development through inhibiting the tumor cell proliferation [ 96 ]. Other studies also demonstrated anti-VEGF (or VEGFR) had conspicuous function in inhibiting GCT development [ 97 , 98 ].…”
Section: Discussionmentioning
confidence: 99%
“…New treatment strategies need to be explored. The employment of anti-VEGFA antibody in mouse model successfully slowed the tumor development through inhibiting the tumor cell proliferation [ 96 ]. Other studies also demonstrated anti-VEGF (or VEGFR) had conspicuous function in inhibiting GCT development [ 97 , 98 ].…”
Section: Discussionmentioning
confidence: 99%
“…Such findings suggest the development of new therapeutic strategies targeting Δψ m to more specifically treat aGCTs, in comparison to EOCs. Although there is limited clinical data focused solely on aGCTs, others have also described glycolytic signatures [ 32 ], with promising initial studies in mural models of GCTs [ 33 ], however the GCT field remains sparse, in comparison to EOCs. The availability of the KGN cell line to model aGCTs in vitro provides an important opportunity to characterize new basic research strategies, such as deciphering the role played by mitochondria as a hub of cellular signaling in response to cytotoxic treatment, independent of small clinical cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that over-expression of SLC25A37 causes cancer-related fatigue in patients with non-metastatic prostate cancer during external beam radiation therapy (Hsiao et al 2013). It is important to note that although we showed that over-expression of miR-22 leads to decreased expression of MXI1 and SLC25A37 , we did not perform the same functional study on the expression of the remaining 37 (potential target) genes, some of which are supported by previous studies such as the reduction of tumor cell proliferation when Vascular Endothelial Growth Factor A ( VEGFA ) was targeted in mouse model with ovarian granulosa cell tumor (Tsoi et al 2013). Additional studies of miR-22 and its target genes in cancers and other pathological contexts are warranted.…”
Section: Discussionmentioning
confidence: 66%